NEW YEAST STRAINS FOR ALCOHOLIC FERMENTATION AT HIGHER SUGAR CONCENTRATION - Bertolini, Maria Celia [UNESP]; ERNANDES, JR; Laluce, Cecília [UNESP] (Chapman Hall Ltd, 1991)
New yeast strains for alcoholic fermentation were isolated from samples collected from Brazilian alcohol factories at the end of the sugar cane crop season. They were selected by their capacity of fermenting concentrated sugar cane syrup as well as high sucrose concentrations in synthetic medium with a conversion efficiency of 89-92%. The strains were identified as Saccharomyces cerevisiae.